METTL3/IGF2BP3-regulated m6A modification of HYOU1 confers doxorubicin resistance in breast cancer - Zhou, Shaocheng; Sheng, Lijuan; Zhang, Lin; Zhang, Jianan; Wang, Lei (Biochimica et biophysica acta. General subjects, 2024)
Chemoresistance is a main reason for therapeutic failure and poor prognosis for breast cancer (BC) patients, especially for triple-negative BC patients. How the molecular mechanisms underlying the chemoresistance to doxorubicin (Dox) in BC is not well understood. Here, we revealed that METTL3/IGF2BP3-regulated m6A modification of HYOU1 increased Dox resistance in BC cells. CCK-8 and Annexin V-FITC/PI staining assays were employed to measure viability and cell death. Western blotting and qRT-PCR assays were applied to assay the expression of genes. Knockdown and rescue experiments were used to assay the role of METTL3, IGF2BP3 and HYOU1 in regulating BC cell responses to Dox. RIP, MeRIP and dual-luciferase activity assays were applied to examine the function of METTL3/IGF2BP3 in the m6A modification of HYOU1 mRNA. It was found that global mRNA m6A methylation levels were upregulated in Dox-resistant BC cell lines. The methyltransferase METTL3 was upregulated in Dox-resistant BC cell lines, and downregulation of METTL3 could overcome this resistance. Furthermore, HYOU1 was identified as a downstream target of METTL3-mediated m6A modification. Downregulation of HYOU1 could overcome Dox resistance, while forced expression of HYOU1 resulted in Dox resistance in BC cells. METTL3 cooperated with IGF2BP3 to modulate the m6A modification of HYOU1 mRNA and increase its stability. Collectively, our findings unveiled the key roles of the METTL3/IGF2BP3/HYOU1 axis in modulating Dox sensitivity in BC cells; thus, targeting this axis might be a potential strategy to increase Dox efficacy in the treatment of BC.